EMPOWERING COMMUNITIES THROUGH THE 'BANYU BIRU ANDARU' CLEAN WATER EMPOWERMENT PROGRAM: A CASE STUDY OF PT BORNEO INDOBARA'S INITIATIVE IN ANGSANA SUB-DISTRICT, TANAH BUMBU - Dindin Makinudin; Silvyna Aditia; Bilqis Nabila; Muhammad Rifqi Zakaria (LPPM Universitas Bina Bangsa, 2024)
This qualitative descriptive study provides a comprehensive examination of the effects of PT Borneo Indobara's Corporate Social Responsibility (CSR) initiative,